Measuring an emotional connection to nature among children - Silvas, Daniel Villalobos, author; Bruyere, Brett, advisor; Vaske, Jerry, committee member; Teel, Tara, committee member; Banning, James, committee member (Colorado State University. Libraries, 2013)
There is a growing concern from scientists and others that children today are losing their connection with nature. The degree of connectedness to nature (CN) has been hypothesized to influence a person's willingness to protect it. Unfortunately, tools used to measure CN are in their infancy and have mostly been developed for adult populations instead of children where most environmental education efforts are targeted. The purpose of this dissertation was to create a reliable and valid measure of a child's emotional connection with nature and study its influence on pro-environmental behaviors. This dissertation includes three studies presented as journal articles (chapters 2-4) and begins with presentation of the theory and frameworks used as the basis for the rest of the manuscript (chapter 1). Chapter two presents the development of a reliable and valid measure of an emotional connection to nature for children. Chapter three validates the structure of the emotional connection to nature scale (ECNS) and demonstrates its predictive potential on attitudes to protect nature (ATPN) and willingness to protect nature (WTPN). Chapter four presents findings from analyses of focus groups among children describing their connection to nature. Chapter five connects these studies by discussing the significance of this work, how this work can be applied and concludes with recommendations for future research.
Keywords: attitudes toward nature; willingness to protect nature; emotional dispositions; connection to nature